2020
DOI: 10.1039/d0ra03426f
|View full text |Cite
|
Sign up to set email alerts
|

Application of polyethylenimine-coated magnetic nanocomposites for the selective separation of Cs-enriched clay particles from radioactive soil

Abstract: Selective separation of Cs-enriched fine particles from contaminated soil using Fe3O4-PEI nanocomposites and a mesh filter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 36 publications
0
4
1
Order By: Relevance
“…In addition, the obtained composite exhibited negative zeta potential values in a wide range of solution pH (i.e., ∼5 to ∼11). Unlike other previous studies, the composite containing GA-PEI moieties revealed positive zeta potential values mainly due to the presence of an amine-rich structure. For this study, the decrement of zeta potential, including the presence of negative zeta potential values, could be due to the combination between the hydroxy/amines-mixed structure of GA-PEI polymer and the MgFe 2 O 4 @SiO 2 NPs.…”
Section: Resultscontrasting
confidence: 61%
See 1 more Smart Citation
“…In addition, the obtained composite exhibited negative zeta potential values in a wide range of solution pH (i.e., ∼5 to ∼11). Unlike other previous studies, the composite containing GA-PEI moieties revealed positive zeta potential values mainly due to the presence of an amine-rich structure. For this study, the decrement of zeta potential, including the presence of negative zeta potential values, could be due to the combination between the hydroxy/amines-mixed structure of GA-PEI polymer and the MgFe 2 O 4 @SiO 2 NPs.…”
Section: Resultscontrasting
confidence: 61%
“…Usually, the cross-linking reaction of PEI using GA as a cross-linker is mainly proposed via route 1. Several studies reported that the successful syntheses of the composites composed of GA-cross-linked PEI system provided the final products containing amine-rich structures (i.e., primary, secondary, and tertiary amines). , Importantly, the findings from these studies motivated us to select this composite system for adsorption of 2,4-D since we expected to take advantage of the presence of these amines for use as binding sites for the 2,4-D molecule. However, the selected synthetic condition in this study probably provided the GA-PEI polymer possessing mixed functional groups (i.e., hydroxy and amines) since several characterization results (i.e., FTIR, NMR, and functional group analyses) indicated not only the presence of amines but also the existence of hydroxy groups in the composite.…”
Section: Resultsmentioning
confidence: 99%
“…The elevated isoelectric point also means that more ion exchange occurs between nano-Fe 3 O 4 and the coated polymer, which results in magnetic composites with more functional groups. This significantly broadens the applicability of nano-Fe 3 O 4 [56][57][58].…”
Section: Nano-fe 3 O 4 Particle Preparationmentioning
confidence: 96%
“…Polyethylenimine was used to stabilize spherical magnetic iron (Fe 3 O 4 ) particles (average size, 10 nm) by Kim et al [57] who then demonstrated the ability of these nanomaterials to connect to and remove clay particles from a soil suspension. The clay particles examined in this case demonstrated a strong efficiency for radioactive cesium ( 137 Cs) ions.…”
Section: Surface Modification Of Magnetic Nanoparticlesmentioning
confidence: 99%